A Bifunctional Fluorescence Probe Based on AIE-ICT Strategy for Visual Detection of Cu2+/Co2+ in Complex Matrix - Jingtao Zhao; Jiaxin Lian; Wenyue Pan; Jialing Du; Ziteng Liu; Longshan Zhao (Molecules, 2023)
A novel fluorescence chemical sensor-based probe 1-{[(E)-(2-aminophenyl)azanylidene]methyl}naphthalen-2-ol (AMN) was designed and synthesized, which performed a “naked eye” detection ability toward Cu2+ and Co2+ based on aggregation-induced emission (AIE) fluorescence strategy. It has sensitive detection ability for Cu2+ and Co2+. In addition, the color changed from yellow-green to orange under the sunlight, realizing the rapid identification of Cu2+/Co2+, which has the potential of on-site visual detection under the “naked eye”. Moreover, different “on” and “off” fluorescence expressions were exhibited under excessive glutathione (GSH) in AMN-Cu2+ and AMN-Co2+ systems, which could be employed to distinguish Cu2+ from Co2+. The detection limits for Cu2+ and Co2+ were measured to be 8.29 × 10−8 M and 9.13 × 10−8 M, respectively. The binding mode of AMN was calculated to be 2:1 by Jobs’ plot method analysis. Ultimately, the new fluorescence sensor was applied to detect Cu2+ and Co2+ in real samples (tap water, river water, and yellow croaker), and the results were satisfying. Therefore, this high-efficiency bifunctional chemical sensor platform based on “on–off” fluorescence detection will provide significant guidance for the advance development of single-molecule sensors for multi-ion detection.